High blood metal ion levels in 19 of 22 patients with metal-on-metal hinge knee replacements: A cause for concern - Laitinen, Minna; Nieminen, Jyrki; Reito, Aleksi; Pakarinen, Toni-Karri; Suomalainen, Piia; Pamilo, Konsta; Parkkinen, Jyrki; Lont, Tonis; Eskelinen, Antti (Acta orthopaedica, 2017)
Background and purpose - There has been increasing alarm regarding metal-on-metal (MoM) joint replacements leading to elevated levels of metal ions and adverse reactions to metal debris (ARMDs). There is little information available concerning the prevalence of and risk factors for these adverse reactions, except with MoM hip joint replacements. We determined the levels of metal ions in blood and the rate of revision due to ARMDs in patients treated with MoM hinge total knee arthroplasty (TKA). Patients and methods - 22 patients with TKAs and MoM hinge connecting mechanisms were studied for whole-blood chromium and cobalt levels at 6 months, 1 year, and/or ≥2 years after surgery. Possible ARMDs were investigated by MRI. 12 patients with TKAs and metal-on-polyethylene (MoP) connecting mechanisms served as controls. Results - The cobalt levels were over 5 ppb in 19 of the 22 patients in the MoM group and in 1 of the 12 patients in the MoP group. The chromium levels were over 5 ppb in 11 of the 22 patients in the MoM group and in none of the 12 patients in the MoP group. Pseudotumors were operated in 4 of the 22 patients in the MoM group and in none of the patients in the MoP group. Interpretation - Our results clearly show that the MoM hinge TKA carries a high risk of increased levels of systemic metal ions and also local ARMD, leading to complicated knee revisions. We therefore discourage the use of MoM hinge TKA.